The influence of a karate training in motor and cognitive functions in older with mixed dementia - Paiva, Ana Clara de Souza; Viana, Eduardo Dias; Andrade, Larissa Pires de; Costa, Thais Delamuta Ayres da; Costa, José Luiz Riani (Acta Fisiátrica, 2014)
Among the different forms and recent non-pharmacological interventions for dementia patients already performed in Brazil, there are no studies that have investigated the effect of a protocol of karate in patients with this clinical conditions, more specifically in the elderly with a diagnosis of mixed dementia, Alzheimer’s disease associated with vascular dementia. Objective: Thus, the present study aimed to analyze the effects of a karate training in cognitive and functional with an elderly mixed dementia. Method: The participant, clinically diagnosed with mixed dementia, underwent a anamnesis, followed by cognitive and functional assessment, pre and post training four months. The karate training was adapted and systematized, in order to muscle strengthening, flexibility, posture techniques, attack (punches and kicks), blocks (defenses) and kata (imaginary fight with multiple opponents), three times per week, lasting an hour session on nonconsecutive days. Results: The findings were maintaining cognitive function and improvement in static and dynamic balance. Conclusion: It was concluded that training adapted and systematized karate contributes to improved static and dynamic balance and maintenance of cognitive status. May, thus contribute to a new alternative non-pharmacological intervention in elderly patients with mixed dementia.